PENINGKATAN HASIL BELAJAR BIOLOGI SISWA KELAS X4 MAN LUWU KAB. LUWU MELALUI PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY (TSTS) - Erniati M (Jurnal Ilmiah Pena: Sains dan Ilmu Pendidikan, 2022)
This research is a classroom action research aimed at improving student biology learning outcomes through the application of cooperative learning TSTS. The study was conducted at MAN Suli Kab. Luwu in the Odd Semester of the academic year 2022/2023 in July-August 2022 with the Research Subject is a student class X4 consisting of 25 students. The study consists of 2 cycles and the collected data is analyzed using quantitative analysis. The results of the study showed that in cycle I, the acquisition score was 90,00 and in the cycle II, the value gain was increased to 100,00, instead there was an increase in the lowest score from cycle 1 by 45,00 to 65,00 in the Cycle II. The research data also showed that the data of students in the non-exhaustive category decreased from 32.00% in cycle I to 8.00% on cycle II instead there was an increase in the number of students entering in the exhaust category with a 68.00% percentage of exhaustiveness in cycles I to 92.00% at cycle 2. From the results of this study, it can be concluded that there has been an increase in the learning outcome of students of class X4 MAN Luwu Kab. Luwu through the application of Cooperative Learning Model Type Two Stay Two Stray (TSTS)Keywords: Biology learning results, TSTS cooperative learning